Detection of pre-eruptive seismic velocity variations at an andesitic volcano using ambient noise correlation on 3-component stations: Ubinas volcano, Peru, 2014 - Machacca Puma, Roger (2019)
Volcano monitoring and eruption forecasting are based on the observation and joined interpretation of several precursory phenomena. It is thus important to detect new types of precursor and to study their relationship with forthcoming eruptions. In the last years, variations of seismic velocity have been observed in some volcanoes, mainly basaltic, before eruptions. In this paper, we look for velocity variations andwaveform decorrelations before the 2014 eruptive sequence of the andesitic Ubinas volcano in Peru. We compute velocity changes by using seismic ambient noise cross-correlation (between pairs of stations) and cross-components correlation (between vertical and horizontal components of single stations), aswell as coda wave interferometry of seismicmultiplets. With these different approaches, we show that the major explosions that occurred from 13 to 19 April were preceded by a clear velocity decrease andwaveformdecorrelation. The amplitude of velocity change is generally larger on single-station cross-components correlation than on two-station cross-correlation in all the frequency ranges tested (between 0.1 and 8 Hz).We highlight an apparent anisotropy of velocity change in singlestation cross-components correlation, with larger amplitudes when correlating vertical and tangential components than using vertical and radial components with respect to the crater. The Mw = 8.1 Iquique earthquake on 1 April 2014 produced also a marked co-seismic velocity drop detected in a high frequency range(3–5 Hz) in both single-station cross-components correlation and cross-correlations. We locate in the horizontal plane and in depth the velocity perturbation and the structural change related with decorrelation. During the main phase of eruptive activity, the velocity decrease at low frequency (0.1–1 Hz) appears to affect the whole edifice mainly at depth of about 1 to 3 km below the surface. The structural perturbation is more concentrated on the south flank of the volcano, a zone that corresponds to an ancient collapse. We suggest that the observed velocity variations are due to the dilatation of the edifice and tomicrofracturation induced bymagma pressurization. The structural change may be locally enhanced by a possible zone of material weakness in the southern sector. The co-seismic velocity perturbation is located mostly in the southeast flank, at depth smaller than 0.5 to 1 km, and may be related to the presence of the hydrothermal system of the volcano. Diques máficos asociados a la ocurrencia de elementos de tierras raras (REE) emplazados en los batolitos de Coasa, Limbani y Aricoma, sur del Perú